Characteristic strength of Gigantochloa scortechinii (or Buluh Semantan) of Malaysian species - Mohd Khairul Kamarudin; Zakiah Ahmad; Hazrina Mansor; Yazmin Sahol Hamid; Khairul Anuar Shahid; Kribanandan Gurusamy Naidu (Penerbit Universiti Kebangsaan Malaysia, 2024)
Bamboo has been identified as a future material for the primary, secondary, and tertiary sectors of the economy with reference to the Bamboo Industrial Development Action Plan in Malaysia 2021-2030 as bamboo is a natural material with high mechanical qualities and a quick reproduction rate. To support this vision, the construction industry needs structural design values. Currently the structural design values for structural bamboo for Malaysian species are not yet available as most of the R&D is focused on the upstream study and non-structural products. Therefore, this study investigates the physical and mechanical properties of a structural bamboo species namely Buluh semantan (Gigantochloa scortechinii) that is the prominent species being used in structural applications. The preparation of specimens and the physical and mechanical testing; bending, shear and compression in direction parallel to the fiber were conducted in accordance with ISO 22157. The properties obtained were used to derive the characteristic capacity of each property. The determination of allowable stresses is based on the characteristic capacity at 5th percentile in accordance with BS EN14358. These derived outputs provide new design data based on capacity grading for Malaysian bamboo and provide alternative environmental-friendly and sustainable construction materials. The results will be soon incorporated in the ISO Standard. This is aligned with the vision to foster green and sustainability building.